"In My Dream She Finds Me…And She Wants Me Just the Way I Am": Fatherhood Experiences of Unmarried Men in South Africa. (December 2016) - Lesch, Elmien; Kelapile, Chandapiwa
Limited research is available with regard to the experience of biological fathers who are interested in being involved in their children's lives but are restricted from doing so. In this study, we aimed to contribute to understanding these paternal constraints and to give unmarried fathers a platform to voice their experiences regarding restricted contact with their children. Interviews were conducted with six single, Setswana-speaking black fathers in South Africa. The phenomenological analysis revealed fatherhood to be an unplanned event at an early age; the cultural responsibilities and conventions regarding marriage and children, and the role these played in restricting contact; constructions of fathers as financial providers; and fathers' emotional experience of restricted access to their children. We conclude that constraining fatherhood constructions make it difficult for fathers, and also mothers and grandparents, to conceive of fathers' contributions beyond financial provision. These constructions curtail unmarried fathers' involvement with their children.